2022
DOI: 10.1021/acs.energyfuels.2c03676
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Evolution of Compressibility and Gas Permeability of Sediments after Hydrate Decomposition under Effective Stress

Abstract: The effective stress and types of particles significantly affect the permeability of hydrate sediments. In this study, effects of hydrate saturation, hydrate decomposition, effective stress, and particle type on gas permeability and sample deformation of montmorillonite samples and quartz-montmorillonite mixtures were investigated. The results showed that the gas phase permeability increased with hydrate formation. In addition, the decline of sample porosity is the fundamental factor determining the permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The obtained effective permeability can equally represent the relative permeability by using the acquired data for mathematical calculations. Relative permeability is defined as the ratio of effective permeability to absolute permeability k eg = 2 p a q g μ g L A ( p 1 2 p 2 2 ) × 10 2 k ew = q w μ w L A ( p 1 p 2 ) × 10 2 where k eg and k ew are the gas effective permeability and the water effective permeability (mD), respectively, p a is the atmospheric pressure (MPa), q g and q w are the gas flow rate (standard cubic centimeter (sccm)) and water flow rate (mL/min), respectively, μ g and μ w are the dynamic viscosity of gas and water (mPa·s), respectively, L is the length of the sample (cm), A is the cross-section of the sample (cm 2 ), and p 1 and p 2 are the inlet pressure and outlet pressure (MPa), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained effective permeability can equally represent the relative permeability by using the acquired data for mathematical calculations. Relative permeability is defined as the ratio of effective permeability to absolute permeability k eg = 2 p a q g μ g L A ( p 1 2 p 2 2 ) × 10 2 k ew = q w μ w L A ( p 1 p 2 ) × 10 2 where k eg and k ew are the gas effective permeability and the water effective permeability (mD), respectively, p a is the atmospheric pressure (MPa), q g and q w are the gas flow rate (standard cubic centimeter (sccm)) and water flow rate (mL/min), respectively, μ g and μ w are the dynamic viscosity of gas and water (mPa·s), respectively, L is the length of the sample (cm), A is the cross-section of the sample (cm 2 ), and p 1 and p 2 are the inlet pressure and outlet pressure (MPa), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Relative permeability is defined as the ratio of effective permeability to absolute permeability. 62 k…”
Section: Permeability Measurementmentioning
confidence: 99%
“…The above studies show that the mechanical properties of hydrate formations are the result of multiple factors, including formation type, hydrate saturation, and experimental conditions, 38,39 among which the formation type is the main factor affecting the mechanical response. 40 The formation skeletons used in previous studies were mostly manual configurations in the laboratory rather than actual samples from the South China Sea strata.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 In addition, with the dissociation of methane hydrate, it is found that the permeability of clays (montmorillonite, illite, and kaolin) decreases, and the permeability damage degree of the three clays first and then decreases. 40,41 Liu et al achieved the reformation of methane hydrate in marine soil sediments and investigated the effect of the reformation of methane hydrate on the gas permeability of sediments, which is of great significance for methane hydrate exploitation in the South China Sea. 42 The above research results of hydrate permeability are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results show that the relationship between permeability and effective stress of montmorillonite is more in line with exponential function. With the increase of methane hydrate saturation, the compressibility of montmorillonite sediments is gradually enhanced. , In addition, with the dissociation of methane hydrate, it is found that the permeability of clays (montmorillonite, illite, and kaolin) decreases, and the permeability damage degree of the three clays first and then decreases. , Liu et al achieved the reformation of methane hydrate in marine soil sediments and investigated the effect of the reformation of methane hydrate on the gas permeability of sediments, which is of great significance for methane hydrate exploitation in the South China Sea . The above research results of hydrate permeability are summarized in Table .…”
Section: Introductionmentioning
confidence: 99%